Doctrinal dangers facing Muslim children in the West and Islam’s position on it (Journal of Human Sciences, 2025)
The sts The study addresses the sources of the dangers faced by the children of Muslims in the West, in light of the attacks and conflicts against Islam and Muslims of all false religions, movements, and sects. This descriptive, analytical, study addresses these dangers that affect the faith, shows their sources, and their impact on the faith of the children of Muslims in the West, and the study iindicates that the Islamic doctrine is one great, correct, and stable because it is derived from the Qur’an, the Sunnah, and the work of the nation’s predecessors, so Muslims must raise their children on it, and that the children of Muslims in the West live in a great clash between the Islamic religion and the decadent Western reality, with claims of freedom and openness, and Western society is not adequately prepared for Muslim children to practice the rituals of their religion and belief, safe from influence and deviation. Sources of danger to the faith affect the children’s belief, such as marriage to a non-Muslim woman, and the entry of converts into Muslim homes, Western education based on material science, and the Muslim family in the West has a difficult task to maintain the doctrine of their children from being influenced by false beliefs.Islam has made clear that the education of Muslim children in Western schools poses a great danger to the children’s faith, and that freedom in the West means freedom from religion, values, and morals. The means of confronting these dangers will not be through individual action, but rather requires collective action, but it begins with the family.The most important recommendations: The situation of Muslims in the West requires more descriptive studies, paying attention to this group of Muslims who face a greater danger to their faith than other Muslim children in Islamic countries. Enhancing and awareness of Muslim communities in Western societies about the doctrinal dangers, requiring Islamic schools in the West to offer free education.To alleviate the burden on the Muslim family, prepare Islamic committees that are informed and empowered to follow up on Islamic curricula and issues for Muslims in the West.